Plan estratégico para mejorar la gestión administrativa en la empresa de abastos Marcel - Cepeda León, Jhon Abel (2023)
The present investigation had as general objective to elaborate a strategic plan to improve the administrative management in the company of Abastos Marcel. For the diagnostic process, an investigation with a mixed approach (qualitative and quantitative) was developed, in addition to being descriptive. For the collection of information, a survey was applied to the company's clients, the managers and the administrative head were interviewed, as well as the most senior seller. The results showed that there is not enough staff, customers wait a long time to be served, and service is slow. On the other hand, training is required for sellers to improve customer service, since errors are made in the invoice, since more than what is due is charged. For this reason, the strategic plan focused on four relevant aspects: the automation of the company, the restructuring of the administrative area, the training of personnel and the implementation of a quality system. Finally, it was concluded that by addressing these problems and strengthening the weaknesses, the company will be able to take advantage of the opportunities and overcome the threats, to improve its position in the market.